Impact of the new EASO obesity definition on the detection of atheromatosis in subjects with low-to-moderate cardiovascular risk - León-Mengíbar, Josep; Bermúdez-López, Marcelino; Valdivielso, José Manuel; Pamplona, Reinald; Torres, Gerard; Mauricio, Dídac; Castro-Boqué, Eva; Fernández, Elvira; Caixàs, Assumpta; Bueno, Marta; Ciudin, Andreea; Hernández, Marta; et al. (Frontiers in Endocrinology, 2025)
BackgroundTraditional body mass index (BMI) does not adequately reflect adipose tissue distribution and associated cardiovascular (CV) risk. To improve risk stratification, the European Association for the Study of Obesity (EASO) proposes to extend the diagnosis of obesity to include individuals with a BMI of 25–30 kg/m², a waist-to-height ratio (WtHR) ≥0.5, and any obesity-related complication.ObjectiveTo examine whether this new definition of obesity can better identify the presence of subclinical atheromatosis disease (SAD) in terms of arterial plaque burden compared to the classical BMI-based definition.MethodsA cross-sectional including 8,330 participants from the ILERVAS project (ClinicalTrials.gov Identifier: NCT03228459), aged 45–70 years with low-to-moderate CV risk and no previous CV disease, was included. Obesity was classified using traditional (BMI ≥ 30 kg/m²) and new definitions. Atherosclerosis was assessed through Doppler ultrasound of carotid and femoral arteries. Logistic regression models adjusted for cardiovascular risk factors were used to evaluate associations between obesity definitions and SAD.ResultsThe new definition increased obesity prevalence from 37.2% to 71.7%. It also revealed higher detection of atheromatous plaques (72.9% vs. 68.6%, p < 0.001) and affected more vascular territories. Multivariable analysis showed the new definition independently predicted overall plaque presence (OR 1.54, 95% CI 1.22–1.94, p < 0.001) and femoral atherosclerosis (OR 1.36, 95% CI 1.10–1.68, p = 0.004). Similar results were obtained when only WtHR was considered, excluding obesity-related complications.ConclusionThe new obesity definition identifies more efficiently individuals at risk for atherosclerosis, especially in the femoral region, compared to the classic BMI definition. Further studies to assess the cost-effectiveness of this approach seem warranted.